A novel evaluation method of natural gas hydrate saturation in reservoirs based on the equivalent medium theory - Qiangui Zhang; Quanshan Li; Xiangyu Fan; Yufei Chen; Zhaoxiang Wang; Bowei Yao; Na Wei; Jun Zhao (Geomechanics and Geophysics for Geo-Energy and Geo-Resources, 2024)
Abstract Natural gas hydrate saturation (NGHS) in reservoirs is one of the critical parameters for evaluating natural gas hydrate resource reserves. Current widely-accepted evaluation methods developed for evaluating conventional natural gas saturation in reservoirs, to some extents, are not sufficient enough to obtain accurate predicted results. In light of the equivalent medium theory, the natural gas hydrate is regarded as the fluid (Mode A) when NGHS is relatively low, while it is regarded as the rock matrix (Mode B) when NGHS is high. Two mathematical model are then developed for evaluating NGHS at Mode A and B. Experimental verification shows that R 2 of the predicted results based upon the proposed model is 0.968, and the average absolute relative error percentage is 8.90%. The error of the predicted results gradually decreases with increasing NGHS, whereas increases with increasing confining pressure. In addition, the proposed model has been applied to the 142.9–147.7 m well section of Well DK-1 in the permafrost region, Qilian Mountains. The results show that the error of the predicted results is less than 13.92%, with its average error being 10.51%. The predicted value gradually increases with its error decreasing as the depth continues to increase, which is consistent with the change behavior of measured data. NGHS evaluation method proposed in this paper fully considers the occurrence form of natural gas hydrate in reservoirs. The model parameters are easy to determine and the predicted results are reliable.